2011
DOI: 10.1519/jsc.0b013e3181dc4571
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Inflammatory Responses to Different Types of Sprint Interval Training

Abstract: We evaluated the effect of different types of sprint interval sessions on the balance between anabolic and catabolic hormones and circulating inflammatory cytokines. Twelve healthy elite junior handball players (17-25 years) participated in the study. Exercise consisted of increasing distance (100 m, 200 m, 300 m, 400 m) and decreasing distance (400 m, 300 m, 200 m, 100 m) sprint interval runs on a treadmill (at random order), at a constant work rate of 80% of the personal maximal speed (calculated from the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 19 publications
6
57
0
1
Order By: Relevance
“…Consistently, previous reports showed that high-intensity exercise was associated with increase of proinflammatory cytokines, for example, IL-6 and TNF- [40][41][42], which have been proposed as mediators of pathologies in humans and have been shown to be associated with an unfavourable metabolic profile with implications for inflammation and cardiovascular disease risk [12]. Furthermore, exercise induces a general stress response involving the activation of the immune systems and may induce immunosuppression in the recovery period and continues to increase after exercise [12,41].…”
Section: Discussionsupporting
confidence: 90%
“…Consistently, previous reports showed that high-intensity exercise was associated with increase of proinflammatory cytokines, for example, IL-6 and TNF- [40][41][42], which have been proposed as mediators of pathologies in humans and have been shown to be associated with an unfavourable metabolic profile with implications for inflammation and cardiovascular disease risk [12]. Furthermore, exercise induces a general stress response involving the activation of the immune systems and may induce immunosuppression in the recovery period and continues to increase after exercise [12,41].…”
Section: Discussionsupporting
confidence: 90%
“…All procedures received local ethics committee approval. Before conducting the study we checked the sample size needed (n = 6) to guarantee 80 % power and 5 % significance level, using studies that measured the IL-6 pre-and immediately post-exercise as referenced by similar protocol (lower body high-intensity intermittent exercise) (Meckel et al 2009(Meckel et al , 2011Leggate et al 2010;Arent et al 2010). …”
Section: Subjectsmentioning
confidence: 99%
“…On the other hand, anti-inflammatory cytokine, such as IL-1ra, IL-4, IL-10 and adipopectic exert protective action against an inflammatory sustained response Seelaender et al 2012). However, a small number of studies have explored the alterations on metabolic and inflammatory profiles (immunometabolism profile) by HIIE (Meckel et al 2009(Meckel et al , 2011Gökbel et al 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations